The competitiveness of a public hospital in Poland in the light of changing regulations in the health care sector - Głód, Grzegorz (Ekonomia i Prawo. Economics and Law, 2020)
Motivation: The health care sector in Poland is undergoing a continuous restructuring process that directly affects the functioning of treatment entities, especially hospitals. One of the key changes is the introduction of a system of basic hospital security of health care services. In this context, the question arises about the competitive management of a public hospital in Poland and the use of entrepreneurial management tools and the possible scope of these processes in the current external conditions. The aim of these efforts is to increase the efficiency of the health care sector, better tailor services to social needs, and improve the management of limited resources. Aim: The aim of the article is to assess the possibility of increasing public hospital competitiveness in Poland in the context of new regulations in the health care sector. These regulations concern the method of contracting health services, the rules for admission to their performance and flat-rate financing. The analysis will be carried out based on the analysis of legal acts and using the elements of the integrated enterprise competitiveness model by G. Głód and O. Flak. Results: Formulating recommendations for public hospital managers in the field of raising competitiveness and indicating the possibility of using appropriately adapted tools to assess the competitiveness in the private sector for entities operating in the public sector.